Beyond the Hospital – Bacterial and Fungal Keratitis in Private Ophthalmic Care - Said, Sadiq; Nolte, Oliver; Blaser, Frank; Quiblier, Chantal; Knecht-Bosch, Pascal; Knecht-Bösch, Martina (Klinische Monatsblätter für Augenheilkunde, 2026)
Introduction Infectious keratitis (IK) has been reported as the leading cause of corneal blindness worldwide, but is potentially avoidable by timely and accurate diagnosis followed by appropriate treatment. Bacterial pathogens remain the most frequently isolated organisms in IK. Fungal keratitis, although less common, is often associated with delayed healing and may require prolonged management. While most studies on IK originate from hospital-based settings, little is known about the incidence and characteristics of cases managed in office-based ophthalmic practices.Methods This investigator-initiated, retrospective, single centre chart review investigated cases of bacterial and fungal keratitis managed in an office-based, primary care ophthalmology clinic in Switzerland. We reviewed electronic patient charts for positive bacterial or fungal culture or polymerase chain reaction results, from anterior-segment scrapings and contact lenses. Antimicrobial susceptibility testing of clinically relevant isolates was performed according to the EUCAST guidelines at the time of isolation.Results Between 2014 and 2024, we identified 112 patients, 52 (46.4%), of whom were female. The median (IQR, range) age was 46 (33 to 63, 13 to 94) years. Across all cases, we detected 157 bacterial and 10 fungal isolates. Staphylococcus epidermidis was the most commonly isolated microorganism, followed by other coagulase-negative Staphylococci and Staphylococcus aureus.Discussion This study overviews bacterial and fungal species distribution among keratitis cases encountered in an office-based ophthalmology setting over ten years. The findings illustrate the microbial diversity seen in private practice, with a predominance of staphylococcal species and a small but notable number of fungal isolates. These findings highlight the importance of maintaining local diagnostic vigilance.
Keywords: bacterial keratitis; fungal keratitis; private ophthalmic care; microbiology; infectious keratitis